Recent changes in peer-reviewed dermatology journals - Ahmad Al Aboud; Khalid Al Aboud (Our Dermatology Online, 2012)
Peer-reviewed dermatology journals are essential media for dermatologists and are undergoing many changes to satisfy readers and authors. The number of dermatology journals and new journals that are devoted to dermatology subspecialties that are being published is increasing. This report highlights recent changes in peer-reviewed dermatology journals.